Frontier Leadership and Strategic Governance: A Historical Analysis of Bada Kaji Amar Singh Thapa’s Legacy - Thapa, Madhav (Unity Journal, 2026)
This study examines the strategic leadership of Bada Kaji Amar Singh Thapa (1751–1816), a key figure in Nepal’s western frontier governance during the late eighteenth and early nineteenth centuries. While existing literature on Nepal’s unification and state survival often emphasizes the contributions of King Prithvi Narayan Shah, this article highlights Thapa’s role in integrating military command, civil administration, and ethical governance under conditions of resource scarcity, contested borders, and complex sociopolitical dynamics. Using a qualitative, interpretive historical methodology, the study situates Thapa’s leadership within the frameworks of crisis leadership theory and strategic leadership theory, explicitly defining these analytical lenses and contextualizing them within a pre‑modern Himalayan setting. In a qualitative research design, this paper unfolds how Thapa integrated terrain‑informed operational planning, adaptive defensive tactics, morale‑based leadership, and institutional loyalty to sustain frontier stability and state cohesion. His governance encompassed revenue administration, infrastructure development, and engagement with local intermediaries, exemplifying a model of civil‑military integration attuned to the challenges of small‑state leadership. Building on these insights, the study proposes the Amar Singh Thapa Strategic Leadership Model, a five‑pillar framework comprising resilience under pressure, ethical command, terrain mastery, strategic autonomy, and integrated governance. The findings suggest that Historical insights can productively inform contemporary officer training, doctrinal reflection, and civil‑military coordination in Nepal, emphasizing adaptive, ethically grounded, and context‑sensitive leadership without imposing outdated prescriptions.